The impact of isolation: evolutionary processes in Hoplitomeryx - van der Geer, A.A.E. (Utrecht University, 2014)
The Late Miocene palaeo-island of Gargano, today part of mainland southern Italy, was home to a strongly endemic, strongly disharmonic and depauperate fauna consisting entirely of deer-like ruminants, rodents, pikas, an otter and insectivores, besides reptiles, amphibians and a peculiar avifauna. The ruminants (family Hoplitomerycidae) are mainly characterised by four orbital horns, a nasal (median) horn, sabre-like upper canines and a closed metatarsal gully. Some diagnostic features are shared with other island mammals and thus likely represent secondarily derived characters without phylogenetic value. Hoplitomerycidae also occurred elsewhere on the Abruzzo-Apulia platform as indicated by fossils from Scontrone. Dental characters between the two localities or palaeo-islands differ, and a new genus is erected here to accomodate the species of Scontrone. The genus Hoplitomeryx is restricted to Gargano and is the focus of this thesis. Hoplitomeryx evolved cladogenetically in situ into four species. Three species are new and are formally described here. The species differ mainly in size, body proportions and robustness. They are the outcome of character displacement under relaxed selective pressures during several millions of years. A similar cladogenesis is observed in other mammalian taxa of the same palaeo-island (the rodents Mikrotia and Stertomys, the insectivore Deinogalerix) but not in the birds. Insular mammals typically grow larger or smaller depending on a combination of factors like ancestral body mass, island area and isolation, latitude, type of resource, prey size (for carnivores) and the number of ecologically relevant species. The outcome may thus differ greatly between similar taxa on different islands or between different taxa on similar islands depending on context. This causes much scatter around the trend. The trend appears much more pronounced in the fossil record, likely related to time in isolation. The trend may show fluctuations through time within a lineage when one or more factors (e.g. climate, faunal context) change. However, the genus Hoplitomeryx displays both smaller and larger species in a multispecies assemblage (adaptive radiation). Within fossil insular Cervidae, this is also observed in Candiacervus (Crete) and perhaps Cervus astylodon (Ryukyu Islands). Body size does not converge here towards a hypothetical optimal body size but diverges instead. Unidirectional body size evolution in general is driven by ecological release (due to the absence of predators and competitors) and character displacement (to enter vacant niches). The same may apply to bidirectional body size evolution, with additional extreme niche partitioning. The largest species have a suboptimal build with their very slender, fragile long limb bones with narrow articulation areas, very unlike the massive limb bones with broad articulation areas of mainland large deer of similar wither's height. Such vulnerable species likely would not survive under high-predation regimes. Its extraordinary long limb bones suggest a dietary niche of otherwise unreachable branches and leaves. Hoplitomeryx is an example of island evolution under extremely long isolation. Its evolutionary history agrees with that of other insular species. This includes both the pattern of its body size evolution (adaptive radiation) as well as the evolution of some of its characteristic traits.
Keywords: SDG 13 - Climate Action